Controllable synthesis of biomimetic nano/submicro-fibrous tubes for potential small-diameter vascular grafts. Issue 26 (8th June 2020) - Wan, Yizao; Yang, Shanshan; Peng, Mengxia; Gama, Miguel; Yang, Zhiwei; Deng, Xiaoyan; Zhou, Jianye; Ouyang, Chenxi; Luo, Honglin
Abstract : A novel small-diameter graft consisting of nanofibrous bacterial cellulose and submicrofibrous cellulose acetate was prepared and evaluated in vitro and in vivo . Abstract : Mimicking the morphological structure of native blood vessels is critical for the development of vascular grafts. Herein, small-diameter composite vascular grafts that integrate the nanofibrous bacterial cellulose (BC) and submicrofibrous cellulose acetate (CA) were fabricated via a combined electrospinning and step-by-step in situ biosynthesis. Scanning electron microscopy (SEM) observation shows the nano/submicro-fibrous morphology and well-interconnected porous structure of the BC/CA grafts. It is found that the BC/CA graft with a suitable BC content demonstrates lower potential of thrombus formation and enhanced endothelialization as compared to the BC and CA counterparts. Western blotting and RT-qPCR results suggest that the BC/CA-2 graft promotes endothelialization by improving expressions of genes vWF-1 and CD31 and protein CD31. The in vivo tests demonstrate much lower inflammatory response to the BC/CA graft. These results suggest that the BC/CA graft shows a great potential as an artificial graft for rapid formation of an endothelial cell monolayer.